Variations of phthalate exposure and metabolism over three trimesters. (August 2019) - Li, Jiufeng; Xia, Wei; Wu, Chuansha; Zhao, Hongzhi; Zhou, Yanqiu; Wei, Juntong; Ji, Fenfen; Luan, Hemi; Xu, Shunqing; Cai, Zongwei
Abstract: Maternal exposure to phthalates may cause some adverse health effects on both mother and fetus, but variations of phthalate exposure and metabolism during pregnancy have not been thoroughly characterized. A total of 946 participants were selected from a cohort study conducted in Wuhan between 2014 and 2015 through which they had provided a complete set of urine samples at three trimesters. Eight phthalate metabolites were analyzed in 2838 urine samples. Based on urinary concentrations, various parameters (i.e. phthalate metabolite concentrations, ratios of metabolites of bis(2-ethylhexyl) phthalate (DEHP) in DEHP, and percentages of individual metabolites in total phthalates) were compared over three visits. We observed that levels of phthalate metabolites showed a U-shaped trend across three trimesters. The significant variations in the ratios of DEHP metabolites indicated that the efficiency in metabolizing DEHP declined during pregnancy and less recent exposure occurred in mid-pregnancy. The changes of percentages of individual compound in total phthalates suggested the inconsistent pattern over trimesters. This longitudinal study found that the exposure pattern, exposure timing and metabolic susceptibility varied by trimesters, which suggests that urine samples should be collected at multiple time points and mothers should be especially careful in the early pregnancy. Graphical abstract: Image 1 Highlights: Phthalate metabolite concentrations demonstrated U-trend over three trimesters. The efficiency in metabolizing di-2-ethylhexyl phthalate decreased during pregnancy. More recent exposure occurred on early and late gestational periods. Mothers were more susceptive to DEHP in the early stages of pregnancy. Multiple samples were needed to evaluate phthalate exposure throughout pregnancy. Abstract : Urinary concentrations of phthalate metabolites showed a U-shaped trend across three trimesters. Mothers were more susceptive to phthalate exposure in the early stages of pregnancy.